National clinical guidelines for the diagnosis and treatment of paroxysmal nocturnal hemoglobinuria - A. D. Kulagin; I. A. Lisukov; V. V. Ptushkin; Ye. R. Shilova; N. V. Tsvetaeva; Ye. A. Mikhailova (Онкогематология, 2014)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare acquired clonal blood disorder caused by somatic mutation of the phosphatidylinositolglycan complementation group A gene (PIG-A) in a hematopoietic stem cell. PNH is characterized by chronic intravascular hemolysis, bone marrow failure, thrombosis, renal dysfunction and other severe clinical syndromes. These clinical guidelines include definition, classification, methods and diagnostic criteria of PNH, indications for screening, optimal treatment including targeted therapy with eculizumab, bone marrow transplantation and symptomatic therapy.